Preventive effects of low‐intensity exercise on cancer cachexia–induced muscle atrophy. Issue 7 (27th March 2019) - Tanaka, Minoru; Sugimoto, Ken; Fujimoto, Taku; Xie, Keyu; Takahashi, Toshimasa; Akasaka, Hiroshi; Kurinami, Hitomi; Yasunobe, Yukiko; Matsumoto, Tomohiro; Fujino, Hidemi; Rakugi, Hiromi
ABSTRACT: We hypothesized that low‐intensity endurance exercise might be more effective in preventing cancer cachexia–induced muscle atrophy through both an increase in protein synthesis and a decrease in protein degradation. The purpose of present study was to evaluate the effects and to clarify the mechanism of low‐intensity endurance exercise on cancer cachexia–induced muscle atrophy. Twenty‐four male Wistar rats were randomly divided into 4 groups: control (Cont), Cont plus exercise (Ex), AH130‐induced cancer cachexia (AH130), and AH130 plus Ex. Cancer cachexia was induced by intraperitoneal injections with AH130 Yoshida ascites hepatoma cells; we analyzed the changes in muscle mass and the gene and protein expression levels of major regulators or indicators of skeletal muscle protein degradation and synthesis pathway in the soleus muscles. Low‐intensity exercise inhibited the muscle mass loss through a suppression of the ubiquitin‐proteasome pathway, increased hypoxia‐inducible factor‐1α and phosphorylated AMPK, and inhibited the deactivation of mammalian target of rapamycin pathway in the soleus muscle, which contributed to the prevention of cancer cachexia–induced muscle atrophy. These results suggest that low‐intensity exercise has the potential to become an effective therapeutic intervention for the prevention of cancer cachexia–induced muscle atrophy.—Tanaka, M., Sugimoto, K., Fujimoto, T., Xie, K., Takahashi, T., Akasaka, H., Kurinami, H., Yasunobe, Y., Matsumoto, T., Fujino, H., Rakugi, H. Preventive effects of low‐intensity exercise on cancer cachexia–induced muscle atrophy. FASEB J. 33, 7852–7862 (2019). www.fasebj.org